Cannabis Use and Nonfatal Opioid Overdose among Patients Enrolled in Methadone Maintenance Treatment. (19th February 2021) - Bryson, William C.; Morasco, Benjamin J.; Cotton, Brandi P.; Thielke, Stephen M.
Abstract: Background: Some ecological studies found lower rates of opioid overdose in states with liberalized cannabis legislation, but results are mixed, and the association has not been analyzed in individuals. We quantified the association between cannabis use and nonfatal opioid overdose among individuals enrolled in methadone maintenance treatment (MMT) for opioid use disorder (OUD). Methods: We recruited a convenience sample of individuals enrolled in four MMT clinics in Washington State and southern New England who completed a one-time survey. Descriptive statistics and multivariate logistic regression compared the prevalence and risk of nonfatal opioid overdose in the past 12 months between participants reporting frequent (at least weekly) or infrequent (once or none) cannabis use in the past month. Results: Of 446 participants, 35% ( n = 156) reported frequent cannabis use and 7% ( n = 32) reported nonfatal opioid overdose in the past year. The prevalence of nonfatal opioid overdose was 3% among reporters of frequent cannabis use, and 9% among reporters of infrequent/no use ( p = 0.02). After imputing missing data and controlling for demographic and clinical factors, the likelihood of self-reported nonfatal opioid overdose in the past year was 71% lower among reporters of frequent cannabis use in the past month (adjusted RR = 0.29, 95% CI 0.10–0.80, p = 0.02). Conclusions: Among individuals enrolled in MMT, frequent cannabis use in the past month was associated with fewer self-reported nonfatal opioid overdoses in the past year. Methodological limitations caution against causal interpretation of this relationship. Additional studies are needed to understand the prospective impact of co-occurring cannabis on opioid-related outcomes.